2009
DOI: 10.1123/japa.17.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Senior Games Participation: Benefits, Constraints, and Behaviors

Abstract: The purpose of the article was to examine the physical activity perceptions and behaviors of older adults who were active participants in a statewide senior games (i.e., North Carolina Senior Games; NCSG) program with its focus on year-round involvement through activities in local communities. A random sample of 440 older adults (55 years and older) completed a questionnaire in 2006 about their participation in community-based senior games. A uniqueness of this study is its focus on active older adults, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 25 publications
3
29
0
1
Order By: Relevance
“…Masters Swimming, 2014). Further, much of the recent research on Masters sport, be it quantitative (e.g., Cardenas, Henderson, & Wilson, 2009;Hodge et al, 2008;Santi, Bruton, Pietrantoni, & Mellalieu, 2014;Young, de Jong, & Medic, 2014) or qualitative (Dionigi, Horton, & Baker, 2010;Dionigi et al, 2011;Grant, 2001) has been conducted in or around large-scale events (e.g., World Masters championships, Seniors Games), with very little in-depth research being conducted on athletes in the process of preparing for these events. Thus, the purpose of this study was to explore prevalent psycho-social conditions at play in day-to-day coached Masters swim programs through the examination of Masters swimmers lived experiences within this setting.…”
mentioning
confidence: 99%
“…Masters Swimming, 2014). Further, much of the recent research on Masters sport, be it quantitative (e.g., Cardenas, Henderson, & Wilson, 2009;Hodge et al, 2008;Santi, Bruton, Pietrantoni, & Mellalieu, 2014;Young, de Jong, & Medic, 2014) or qualitative (Dionigi, Horton, & Baker, 2010;Dionigi et al, 2011;Grant, 2001) has been conducted in or around large-scale events (e.g., World Masters championships, Seniors Games), with very little in-depth research being conducted on athletes in the process of preparing for these events. Thus, the purpose of this study was to explore prevalent psycho-social conditions at play in day-to-day coached Masters swim programs through the examination of Masters swimmers lived experiences within this setting.…”
mentioning
confidence: 99%
“…The results of this study indicated that interpersonal factors, namely relationships between rural family members, and their relationships with other community residents were of greatest concern for participants. Following Cardenas, Henderson, and Wilson (2009), we have limited the scope of this article to discuss the findings that relate to interpersonal factors.…”
Section: Fostering New Friendshipsmentioning
confidence: 96%
“…Cardenas, Henderson, and Wilson [57] suggested demographic characteristics may affect older adults’ perceptions of the benefits of sport. Perceived health and physical strength, self-esteem, and likelihood of meeting people were rated more highly among Senior Games participants who lived alone, possessed high school or lower levels of education, and reported an income of $19,000 or less.…”
Section: Rds and Developmental Outcomes Of Sport For Older Peoplementioning
confidence: 99%